Calcified Chronic Subdural Hematoma: A Case Report and Literature Review. Issue 4 (December 2017) - Xiao, Zongyu; Chen, Xiaojuan; Li, Kunzheng; Zhang, Zhengping
Calcified chronic subdural hematoma (CCSDH) is a rare disease that accounts for approximately 0.3%–2.7% of all chronic subdural hematomas (CSDHs). The clinical features of CCSDH are very similar to those of noncalcified CSDH and include headache, decreased alertness, weakness, numbness, gait disturbance, seizures, memory impairment, confusion, and unconsciousness. All symptomatic CCSDH should be treated surgically. Majority of these patients recover well following surgery. In this report, we present the case of a patient with CCSDH who developed severe cerebral edema following its removal, necessitating decompressive craniectomy. Although there were no abnormal findings in laboratory blood tests, and no signs of brain herniation or epilepsy was found the following day after surgery, the patient's family refused all treatment and a postoperative brain computed tomography (CT) scan. The patient was discharged and died at home. Cerebral hematoma and normal perfusion pressure breakthrough (NPPB) may cause severe cerebral edema following the total removal of a CCSDH.